PROTOTYPE ALAT JEMURAN PAKAIAN OTOMATIS MENGGUNAKAN ARDUINO BERBASIS ANDROID - Azis, Afif; Chusyairi, Ahmad (ISTEK WIDURI, 2021)
The clotheslines used by the community are still in manual form so people still have to lift the clothesline directly. People who have a lot of interests or who work will not have time to lift the clothesline directly so they have to leave their more important work. People are still confused about how to lift clotheslines with the uncertain weather when there are other jobs or traveling. Based on these problems, a prototype model of an automatic clothesline was built using an Android-based Arduino Uno, this is to lighten and shorten the time in lifting clotheslines or drying clothes when the weather is changing. The purpose of this research is to make a tool that can help reduce household chores, especially drying clothes automatically using LDR sensors and rain sensors and can be controlled by cellphones. An automatic clothesline tool has been designed using an Android-based Arduino. In making the prototype using the LDR sensor as a light detector, using a water/rain sensor as a rainwater detector and using a servo motor to open and close the clothesline roof, and use the HC-05 Bluetooth module to move the clothesline roof with a cellphone using bluetooth which is controlled with an Arduino microcontroller. UNO which functions as a data processing center. After testing this tool works well, the sensor will check the weather outside whether it is sunny or rainy. When the weather is sunny or hot outside, the roof of the clothesline will automatically open and if it is raining outside, the roof of the clothesline will automatically close. When the water sensor and LDR sensor do not work or experience problems, the automatic clothesline can be controlled with a smartphone that is connected to the HC-05 Bluetooth module. The result of this research is that the automatic clothes drying device using Arduino Uno can ease household chores when drying clothes and based on the test results with the blackbox table the tool runs 100% as desired.